A Novel Two-dimensional Locomotion Scheme of a Micro-robot with Only a Uniform Magnetic Field - Kim, Jinsoo; Kim, Seung-Jong (2014 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2014)
This paper presents a novel motion control method of a micro-robot for biomedical applications. The proposed micro-robot is composed of a permanent magnet with oblique magnetization, and the electromagnetic actuation (EMA) system consists of only two pairs of Helmholtz coils arranged at a right angle on a horizontal plane. While conventional systems generally use the magnetic field gradient for the propulsion, the proposed system uses only a uniform magnetic field. By virtue of these strategies, we can make the system smaller and reduce the power consumption compared to the pre-existing EMA systems. To verify the feasibility of the proposed system, basic experiments and trajectory tracking were performed under different environments.